Relations of Non-Economic Ownership as a Basis of Identification of Social Estates - Tittenbrun, Jacek; Miński, Radomir; Szymańska, Ewelina (Studia Historiae Oeconomicae, 2011)
Just as the theory of economic ownership is a prime tool for identification of social classes as units of social differentiation in the economic structure, so per analogiam it can be said that the theory of non-economic ownership can play such a role in relation to non-economic spheres of society, thus allowing for discernment of a number of status groups. These non-economic ownership relations are manifested in monopolisation by particular status groups of various material and immaterial goods and privileges. So far, as many as 18 such non-economic ownership relationships have been identified. The aim of the research is to describe and analyse social diversity of contemporary residents of Poznań. In our article we focus on the empirically identified status groups.